Jardins imaginaires en partage - Cécile Regnault; Magali Paris (Projets de Paysage)
Imagination is analysed by means of a pedagogical exercise in garden design based on childhood memories conducted with architecture students. After a reminder of the theoretical framework of the environmental autobiography of Clare Cooper Marcus, the theses of Gaston Bachelard concerning topoanalysis and material imagination, and the theories of Gilbert Simondon on the transition from imagination to invention, we study the potential of imagination in designing for and with others. Organised in three phases during a semester, the exercise calls on the performance of creative imagination in three modes: individual and inter-individual creativity, exposure to other influences outside the school, and collective creativity. The approach privileges the shared construction of imaginary spaces. Based on the analysis of the representations produced by students, our perspective as researchers demonstrates how these imaginary spaces are not confined to the virtual world but are situated somewhere between design and production and rely on a form of imagination which focuses on creating rather than reproducing.